EVALUATING VOLUNTARY DISCLOSURE ACCORDING TO GRI REQUIREMENTS AND ITS ROLE IN ACHIEVING SUSTAINABLE DEVELOPMENT - A STUDY OF A SAMPLE OF ISLAMIC BANKS IN THE IRAQI ENVIRONMENT (World Economics and Finance Bulletin, 2025)
This study aimed to clarify the concept of social responsibility accounting and clarify the role of economic units in applying disclosure requirements according to its standards and establishing an approach between the concepts and requirements of contemporary social responsibility accounting with what is stated in it according to the Islamic perspective and to stand on the awareness of economic units of the importance of applying the requirements of social responsibility accounting and its importance to society as a whole and the Islamic culture in particular. The study employed the deductive approach in the theoretical aspect and the inductive aspect in the practical element. The research hypothesis was tested on a sample of Islamic banks by reviewing their annual report for the year 2023 and studying all the expenses and activities referred to in the report and related to social activities by employing a study of the content of the reports and preparing a checklist to assess the commitment to the requirements of GRI and then proceeding to prepare a questionnaire for specialists regarding the importance of voluntary disclosure in achieving sustainable development, to observe the extent of their awareness towards establishing the requirements of social responsibility accounting and its impact on sustainable development with (60) specialists. The research concluded that there is a weakness in the voluntary disclosure of social responsibility requirements for the research sample. It recommended the importance of this disclosure to achieve sustainable development Because it gives the clients and stakeholders confidence in the research sample
Keywords: Voluntary disclosure; GRI requirements; sustainable development; Islamic banks